Hydrogeological Conditions of the "Dhunge Dharas" in the Kathmandu Valley - Karmacharya, R.; Shrestha, S. D.; Rao, G. Krishna (Journal of Nepal Geological Society, 1993)
Groundwater has been tapped in the Kathmandu valley since ancient times through the traditional stone-carved water-spouts called Dhunge Dharas and dug wells. Present study deals with hydrogeological situation of dug wells and Dhunge Dharas. Quality of groundwater is evaluated on the basis of pH versus topography. The Dharas are classified into natural types on slopes and artificial ones in the valley poor. Depth of water table is observed to be between nearly at ground surface to 6m below the sloping ground and exceptionally up to 12.25m below ground level (bg l) on the terraces. Chemical quality of groundwater is found to be good except at a few places.